A bibliometric analysis of NLRP3 inflammasome in acute lung injury/acute respiratory distress syndrome from 2010 to 2021 - Xiao, Zhuoran; Hu, Song; Xu, Wenting; Wang, Sheng; Mo, Wei; Deng, Huimin; Wei, Juan; Yang, Hao; Zhou, Wenyu; Li, Quanfu; Zhou, Huanping; Lv, Xin (Frontiers in Immunology, 2022)
Background Nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is essential in the pathogenesis of acute respiratory distress syndrome (ARDS), a fatal clinical syndrome that deteriorated from acute lung injury (ALI). This bibliometric study aims to offer a thorough insight into the scientific output about NLRP3 inflammasome in ALI/ARDS and explore the intellectual base, developing trajectory and emerging trends. Methods We retrieved the literature from 2010 to 2021 from Science Citation Index Expanded (SCIE) database. Bibliometrix (3.1.4) R package and CiteSpace (5.8.R3) were used for further analysis and visualization. Results A total of 508 English articles and reviews published from 2010 to 2021 were identified. The annual number of publications presented a rapidly developing trend especially in recent years. Among all the 42 countries, China was the most productive and most cited country, while the USA had the greatest impact. Peter A. Ward from the USA was the most productive corresponding author, and 4 of these top 10 corresponding authors were from China. The most cited reference was written by Ahmed (2017) of Zhejiang University in China. The Journal of Immunology had highest citation count and G-index. Furthermore, the major disciplines of research front have drifted from “Medicine, Medical, Clinical” to “Molecular, Biology, Immunology” over the past 12 years. In the co-occurring network, the terms “acute lung injury,” “NLRP3 inflammasome,” “interleukin-1β,” “NF-κB,” and “NLRP3 activation” occurred most frequently, while in burst detection, “oxidative stress” had the highest burst strength. Co-citation network revealed that Cluster 2 “virus infection” was the most active area, including the most citation bursts. Cluster 0 “severe COVID-19” and Cluster 1 “dual inhibitor PTUPB” were emerging themes in recent years, and they involved the largest number of publications. Conclusions This bibliometric analysis revealed a rapid growth trend of the relatively novel topic: NLRP3 inflammasome in ALI/ARDS. China was the largest contributor, while the USA offered the most landmark papers. The major disciplines of research front drifted from “Medicine, Medical, Clinical” to “Molecular, Biology, Immunology.” In recent years, studies about the role of NLRP3 in COVID-19-associated ALI/ARDS and oxidative stress became hot spots.